Sigmatic plurals in Romance varieties spoken in Italy and their interaction with -i plurals - Savoia, Leonardo M.; Baldi, Benedetta; Manzini, M. Rita (LingBaW. Linguistics Beyond and Within, 2018)
In Sardinian, Friulian, Rhaeto-Romance, Occitan (not considered in this work) and Franco-Provençal varieties spoken in peripheral Italian areas, the -i inflection is not totally eradicated but interacts with plural -s. The coexistence of -s and -i reflects syntactic constraints. Specifically, -i is in complementary distribution with -s or it combines with –s, giving rise to a duplicated lexicalization of plurality. In any event, it is specialized for a subset of the morpho-syntactic contexts. The distribution of -i generally involves the D domain, i.e. determiners and clitics. In some cases, -i is limited to the D elements. Different agreement systems on D and on N emerge, recalling partial or asymmetric agreement phenomena known in literature. Moreover, in the relevant varieties (-)i is in turn the inflection of the dative clitic; this suggests that (-)i is endowed with a slightly different content from plural -s, that, on the contrary, shows no connection with dative.